Unconditional quantum teleportation of multi-color continuous-variable states: from near-infrared to telecommunications bands - Gewers, Felipe Lucas (2025)
Quantum teleportation is the basis for numerous quantum applications, with the continuous-variable (CV) protocol having the significant advantage of being unconditional and deterministic, allowing every input state to be teleported. In the context of quantum networks, quantum channels connecting different wavelengths can be used in quantum hybrid technologies, linking different quantum platforms with distinct purposes that interact with light at specific wavelengths. Our approach to building these continuous-variable quantum channels is through quantum teleportation between quadratures of fields at widely different frequencies. To achieve this, we employ a triply resonant optical parametric oscillator (TROPO) operating above threshold as a source of two-mode entangled states. Pumped by a 532 nm Nd:YAG second harmonic laser, the system generates intense beams at 794.4(4) nm (377 THz; near-infrared compatible with the rubidium D1 line) and 1611(3) nm (186 THz; telecommunication L-band), with a frequency separation of 191 THz, which is over one octave. Using the resonator-assisted auto-homodyne technique, we implement the teleportation protocol to transfer a displaced coherent state from the infrared to the telecommunication band. In this work, we report the first demonstration of multi-color continuous-variable (CV) quantum teleportation bridging distinct frequency bands. This also marks the first implementation of teleportation between the sideband modes of intense beams that surpasses the classical fidelity limit. Additionally, we provide the first full characterization of the individual sideband modes in widely separated signal and idler fields generated by an above-threshold optical parametric oscillator. This demonstration paves the way for the development of hybrid quantum systems with enhanced connectivity.